THE CONCEPT OFAKHLAQUL KARIMAHAS A BASIC PRINCIPLE OF CHARACTER BUILDING IN WEST NUSA TENGGARA INDONESIA - Najamuddin Amy , Subagyo Adam , Suparto Wijoyo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to formulate Akhlaqul Karimah’s concept as a fundamental principle of character building among people in West Nusa Tenggara, Indonesia. This research uses qualitative research with the library research method. The results of the study showed that Akhlaqul Karimah is the foundation of moral education. Akhlaqul Karimah concept, according to Al-Ghazali and Ibnu Khaldun, is fundamental and should be disseminated in character-building education. Akhlaqul Karimah’s concept emphasizes morality to Allah SWT, Akhlaq to Parents, Akhlaq to Others, and Akhlaq to the Environment. This concept can contribute to politics and democracy, education, economics, and empowerment of the ummah and environmental preservation.